2019
DOI: 10.1021/acsapm.9b00724
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Functionalized Dextrin-Sodium Alginate Based Fluorescent Sensor: Detoxification of Cu2+ and Ni2+ Ions

Abstract: The research work performed and described here is in regard to synthesis of dextrin-sodium alginate based hybrid hydrogel film. It showed the maximized percentage swelling at 1145% after optimization of all reaction parameters. It was further functionalized with a fluorophore, i.e., riboflavin, to introduce luminescent behavior to the film. The RDSA film can not only remove but also sense the copper and nickel ions in the surroundings very sensitively up to 0.4445 μM and 0.2571 μM, respectively, which is in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…The following references appear in the Supplemental information: Abbasi et al., 2019 ; Abuhatab et al., 2020 ; Ansari et al., 2020 ; Bora et al., 2019 ; Chiou et al., 2020 ; Coldur et al., 2020 ; Darmayanti et al., 2019 ; Fang et al., 2020 ; Feng et al., 2020 ; Ge et al., 2020 ; Ghosh et al., 2019 ; He et al., 2021 ; Hosseinjani-Pirdehi et al., 2020 ; Jiang et al., 2020 ; Jigyasa et al., 2020 ; Joseph et al., 2020 ; Kadian and Manik, 2020 ; Ke et al., 2020 ; Krishnan and Suneesh, 2019 ; Landge et al., 2020 ; Li et al., 2020a ; Li et al., 2020b ; Ma et al., 2020a ; Ma et al., 2020b ; Mal et al., 2020 ; Mathivanan et al., 2020 ; Miao, 2019 ; Nan et al., 2020 ; Podasca et al., 2019 ; Qian et al., 2019 ; Qu et al., 2020 ; Rajalakshmi and Palanisami, 2020 ; Ran et al., 2020 ; Roja et al., 2020 ; Sharma et al., 2019 ; Tian et al., 2019 ; Xiao et al., 2020 ; Xiong et al., 2019 ; Xu et al., 2019 ; Zhu et al., 2020 .…”
Section: Supporting Citationsmentioning
confidence: 99%
“…The following references appear in the Supplemental information: Abbasi et al., 2019 ; Abuhatab et al., 2020 ; Ansari et al., 2020 ; Bora et al., 2019 ; Chiou et al., 2020 ; Coldur et al., 2020 ; Darmayanti et al., 2019 ; Fang et al., 2020 ; Feng et al., 2020 ; Ge et al., 2020 ; Ghosh et al., 2019 ; He et al., 2021 ; Hosseinjani-Pirdehi et al., 2020 ; Jiang et al., 2020 ; Jigyasa et al., 2020 ; Joseph et al., 2020 ; Kadian and Manik, 2020 ; Ke et al., 2020 ; Krishnan and Suneesh, 2019 ; Landge et al., 2020 ; Li et al., 2020a ; Li et al., 2020b ; Ma et al., 2020a ; Ma et al., 2020b ; Mal et al., 2020 ; Mathivanan et al., 2020 ; Miao, 2019 ; Nan et al., 2020 ; Podasca et al., 2019 ; Qian et al., 2019 ; Qu et al., 2020 ; Rajalakshmi and Palanisami, 2020 ; Ran et al., 2020 ; Roja et al., 2020 ; Sharma et al., 2019 ; Tian et al., 2019 ; Xiao et al., 2020 ; Xiong et al., 2019 ; Xu et al., 2019 ; Zhu et al., 2020 .…”
Section: Supporting Citationsmentioning
confidence: 99%
“…Hence, the role of borax as well as glutaraldehyde is con rmed through the data. It is concluded that hydrogel was formed through H-bonding with tetrahydroxyl borate units and imide bond formation among various carbonyl units and amine groups (Priya et al, 2020;Sharma et al, 2020;Sharma et al, 2019a;Priya et al, 2019;Sharma et al, 2019b;Sharma et al, 2019c;Talebian et al, 2019) (Fig. 2f).…”
Section: Ft-irmentioning
confidence: 93%
“…1n). The nal hydrogel consist of imide linkages and borax based H-bonding, hence the basic elements are carbon (51.49 weight% and 53.14 atomic%), oxygen (13.73 weight% and 10.64 atomic%), nitrogen (13.94 weight% and 12.34 atomic%) and boron (20.84 weight% and 23.89 atomic%) (Priya et al, 2020;Sharma et al, 2020) (Fig. 1q).…”
Section: Sem-eds-eds Mappingmentioning
confidence: 99%
“…In recent years, various polymer based engineered materials such as nanocarriers, electrospun fibers, hydrogels, and sensors have been reported in the literature for various applications including sustainable agriculture. , Among various nanoformulations, polymer based nanomaterials or nanocomposites are often explored as carriers of fertilizers/pesticides owing to their high surface areas, high loading efficiencies, and tunable release rate along with their environmental friendliness and biodegradable nature. , On the other hand, electrospun fibers exhibit a porous structure and an extremely high surface-to-volume ratio which facilitate the incorporation of more than one active ingredient simultaneously . Further, polymer based hydrogels possess hydrophilic functional moieties such as OH and COOH in their structures which are capable of holding water molecules inside their hydrophilic pores for a prolonged period . Thus, these hydrogels can help in providing better soil management for effective plant growth.…”
Section: Introductionmentioning
confidence: 99%